Relatório de Estágio Profissional "Aprender e ensinar num ano pleno de desenvolvimento pessoal e profissional" - Óscar Ramires da Silva (2019)
At the end of my academic journey, I find myself on my final challenge, the professional internship. This is the final step on my educational degree, where I put to the test, in a real teaching environment, the knowledge and strategic tools that I have acquired during my educational process. The internship is inserted in the plan of study of the 2nd year degree in Teaching of Physical Education, in the Faculdade de Desporto da Universidade do Porto. On this report, I am putting into words, in the truest form, all of my evolving progress as a teacher, leading two classes with very different work ethics between them. Decision making about planning, realization and evaluation were a part of my weekly routine. My expectations for this year of internship are holistic, as is my will to evolve and grow as a teacher, to be able to respond to my responsibilities, and to my students, to the best of my abilities.